General labour history of Africa : workers, employers and governments, 20th-21st centuries - Bellucci, Stefano; Eckert, Andreas, 1964- (James Currey, 2019)
Co-published with the International Labour Organization on the centenary of its founding in 1919, the General Labour History of Africa is a landmark in the study of labour history. It brings, for the first time, an African perspective within a global context to the study of labour and labour relations. The volume analyses key developments in the 20th century, such as the emergence of free wage labour; the transformation in labour relations; the role of capital and employers; labour agency and movements; the growing diversity of formal and informal or precarious labour; the meaning of work; and the impact of gender and age on the workplace. The contributors - eminent historians, anthropologists and social scientists from Africa, Europe and the United States - examine African labour in the context of labour and social issues worldwide: mobility and colonial and postcolonial migration, forced labour, security, the growth of entrepreneurial labour, the informal sector and self-employment, and the impact of trade unionism, welfare and state relations. The book discusses key sectors such as mining, agriculture, industry, transport, domestic work, and sport, tourism and entertainment, as well as the international dimension and the history and impact of the International Labour Organization itself. This authoritative and comprehensive work will be an invaluable resource for historians of labour, social relations and African history.